(untitled) (Research, Society and Development, 2020)
Introduction: Breast cancer is the type that most affects women worldwide, in Brazil is the most frequent, estimated for the 2018-2019 biennium, 59,700 new cases, while cervical cancer is the fourth most common type. among women, with an estimated 2018-2019 of 16,370 new cases for each year of the biennium, thus the aim of this study was to promote educational interventions aimed at the prevention and early detection of breast and cervical cancer in religious space. Materials and Methods: Action research, using interview and culture circle with 12 evangelical women in a city in the countryside of Maranhão, Brazil. Culture circles promoted dialogues on the themes: what is breast and cervical cancer; disease severity; prevention and diagnosis and were organized to include the reception, coding, decoding and synthesis of the meetings. Results: The following categories emerged: Initial impressions of culture circles; Cancer knowledge; Feelings related to cancer; tests for the diagnosis of breast and cervical cancer; and Decoding knowledge and attitudes about cancer. Discussion: It is possible to prevent breast and cervical cancer by decoding knowledge and attitudes, and it is necessary to adopt strategies that encourage women to seek health services not only in the presence of complaints, but in a preventive and self-care perspective. Conclusions: The dialogue enabled critical unveiling, promoting the adoption of prevention and health promotion practices.